The Singapore Armed Forces and Domestic Security - Lee, Terence (2016)
MINISTER OF Defence Mr. Teo Chee Hean recently tabled in Parliament for a second time the Singapore Armed Forces (Amendment) Bill. The Bill seeks to amend the Singapore Armed Forces (SAF) Act to give the military legal powers when conducting domestic security operations. The revisions to the Act will put in place “a proper legal framework to ensure everything in the conduct of security operations is properly specified, and to lay out clearly what servicemen can and cannot do”.